2019
DOI: 10.1140/epjd/e2019-90692-0
|View full text |Cite
|
Sign up to set email alerts
|

Fall-back time for photo-ionized Cs atoms attached to superfluid 4He nanodroplets

Abstract: We have studied the dynamic evolution of a Cs atom photo-excited from 6s to 6p and 7s states on a helium droplet using time-dependent 4 He-DFT simulations. Depending on the excited electronic state, the Cs impurity remains on the droplet surface or it is ejected. Upon subsequent photo-ionization of the excited Cs atom the resulting Cs + cation may either be ejected or come back to the droplet, depending on the time delay between photo-excitation and photo-ionization. We have calculated the critical time delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(51 citation statements)
references
References 42 publications
18
33
0
Order By: Relevance
“…Using time-dependent 4 He-DFT simulations, the same authors have found that excited-state Cs atoms desorb after excitation to the 6p 2 Σ 1/2 state, while for the 6p 2 Π 1/2 state, the atoms are predicted to desorb from the droplet only if the excitation wavenumber E pump /(hc) is ≥11200 cm −1 . The results of the theoretical studies also imply that CsHe exciplex formation is supported for excitation to the 6p 2 Π 3/2 and 6p 2 Π 1/2 states only, and that the desorption of the exciplex in the 6p 2 Π 3/2 state is due to non-radiative relaxation to the 6p 2 Π 1/2 state [36].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Using time-dependent 4 He-DFT simulations, the same authors have found that excited-state Cs atoms desorb after excitation to the 6p 2 Σ 1/2 state, while for the 6p 2 Π 1/2 state, the atoms are predicted to desorb from the droplet only if the excitation wavenumber E pump /(hc) is ≥11200 cm −1 . The results of the theoretical studies also imply that CsHe exciplex formation is supported for excitation to the 6p 2 Π 3/2 and 6p 2 Π 1/2 states only, and that the desorption of the exciplex in the 6p 2 Π 3/2 state is due to non-radiative relaxation to the 6p 2 Π 1/2 state [36].…”
Section: Resultsmentioning
confidence: 72%
“…The interaction between an electronically excited Cs atom and a He nanodroplet is often repulsive owing to the high delocalization of the valence electron in excited-state Cs [26,35]. The 6p 2 Π 1/2 , 6p 2 Π 3/2 and 6p 2 Σ 1/2 molecular states, which are excited near the 6p ← 6s transitions in atomic Cs, have bound-state character, but resonant excitation near the equilibrium position of the Cs-He N complex is predicted to produce excited-state Cs atoms in molecular states far above the dissociation limit, so that a desorption of the excited Cs atom from the droplet is expected [36]. Using time-dependent 4 He-DFT simulations, the same authors have found that excited-state Cs atoms desorb after excitation to the 6p 2 Σ 1/2 state, while for the 6p 2 Π 1/2 state, the atoms are predicted to desorb from the droplet only if the excitation wavenumber E pump /(hc) is ≥11200 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…These software packages have been designed to become powerful and universal instruments of computational research in the field of MBN Science, which should play a role of a "virtual microscope" and a "camera" capable to explore, simulate, record and visualize both structure and dynamics of the MBN-world with an atomistic level of accuracy, in order to both reproduce its known features and predict the new ones. In this Topical Issue, many contributions [12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] provide case studies conducted with these packages and demonstrate their application to a broad variety of topical areas in MBN science as listed at the beginning of this Editorial. To be noted that these universal and powerful software packages are fully applicable to a broad variety of the topical areas of the MBN Science listed above in the introductory part of the Editorial.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical study [16] investigated helium nanodroplets with impurities. Here the impurities were modeled through cesium atoms and the Coppens et al studied the dynamic evolution of a Cs atom photo-excited from 6s to 6p and 7s states on a helium droplet using timedependent DFT simulations.…”
Section: Clusters and Nanoparticlesmentioning
confidence: 99%
“…27-32, and earlier works have simulated photon absorption spectra of alkali atoms attached to vortex-free helium nanodroplets using different functionals and/or He-alkali pair potentials. [27,28,[33][34][35][36][37] We have repeated them in order to ensure comparison with vortex-hosting droplets with exactly the same parameters. To the best of our knowledge, the spectrum of alkali atoms attached to vortex-hosting droplets has not been previously addressed theoretically.…”
Section: Please Cite This Article As Doi:101063/50008923mentioning
confidence: 99%